2010
DOI: 10.1007/s00540-010-1027-x
|View full text |Cite
|
Sign up to set email alerts
|

Complications with massive sacrococcygeal tumor resection on a premature neonate

Abstract: Resection of large sacrococcygeal teratomas (SCT) in neonates can pose many anesthetic challenges. The pathophysiology of the SCT determines the varying management. We present a case report of a 34-week newborn with a massive Altman type 3 SCT. The surgery was delayed 2 days because of hyperkalemia; however, as a result of continued tumor lysis the patient's condition had worsened with little improvement of the potassium level. During the surgery, the patient had issues of bleeding needing massive transfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Although the mortality rate for newborns with SCT is at most 5%, the mortality rate for fetal SCT exceeds 50%, and fetal SCT associated with non-immune hydrops is uniformly fatal [3]. Predictors of poor outcome include diagnosis before 20 weeks gestation, delivery before 30 weeks, low birth weight, Apgar score less than 7, malignant histotypes, polyhydramnios, placentomegaly and development of hydrops [2]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the mortality rate for newborns with SCT is at most 5%, the mortality rate for fetal SCT exceeds 50%, and fetal SCT associated with non-immune hydrops is uniformly fatal [3]. Predictors of poor outcome include diagnosis before 20 weeks gestation, delivery before 30 weeks, low birth weight, Apgar score less than 7, malignant histotypes, polyhydramnios, placentomegaly and development of hydrops [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Abraham et al [2] has been reported that the manual ventilation and lifting the tumor by surgeon can help with the ventilation. And it is very difficult to maintain body temperature because of the large surface area of the SCT compared to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delaying surgery with the intention of stabilizing the infant in the NICU can lead to worsening hemodynamic status due to persistent shunt physiology or in some cases intratumoral hemorrhage or tumor rupture. Blood loss and massive transfusion requirements can lead to disseminated intravascular coagulation, and transfusion of factor VIIa has been recommended in such cases [25]. Although we recommend complete resection with coccygectomy after the infant has stabilized and grown [21,25,26], it is interesting that early debulking of SCTs has been shown in some cases to result in the disappearance of malignant elements [27].…”
Section: Discussionmentioning
confidence: 99%